2020
DOI: 10.1186/s40814-020-00683-1
|View full text |Cite
|
Sign up to set email alerts
|

Design, rationale and analysis plan for the Stand Up for Health trial in contact centres: a stepped wedge feasibility study

Abstract: Background Contact centres are one of the most sedentary workplaces, with employees spending a very high proportion of their working day sitting down. About a quarter of contact centre staff regularly experience musculoskeletal health problems due to high levels of sedentary behaviour, including lower back pain. There have been no previous randomised studies specifically aiming to reduce sedentary behaviour in contact centre staff. To address this gap, the Stand Up for Health (SUH) study aims t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…We finally included 24 studies, reported in 38 articles ( 30 , 31 , 36 , 48 82 ), in our qualitative synthesis and 18 studies, reported in 29 articles ( 30 , 31 , 36 , 48 51 , 55 59 , 62 , 63 , 65 , 66 , 68 75 , 78 82 ), in our meta-analyses. We identified three potentially relevant ongoing studies, reported in four articles ( 83 86 ). The study selection process including the main reasons for the exclusion of studies after full text screening is shown in a PRISMA flow diagram ( 16 , 87 ) ( figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…We finally included 24 studies, reported in 38 articles ( 30 , 31 , 36 , 48 82 ), in our qualitative synthesis and 18 studies, reported in 29 articles ( 30 , 31 , 36 , 48 51 , 55 59 , 62 , 63 , 65 , 66 , 68 75 , 78 82 ), in our meta-analyses. We identified three potentially relevant ongoing studies, reported in four articles ( 83 86 ). The study selection process including the main reasons for the exclusion of studies after full text screening is shown in a PRISMA flow diagram ( 16 , 87 ) ( figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The SUH study comprised of a preliminary outcome evaluation, undertaken to address objective 1, and a process evaluation to address objectives 2-4. The study used a stepped wedge cluster randomised feasibility trial design [30]. Eleven contact centres were recruited and randomised to one of five unique sequences (Fig 1 ), with each sequence corresponding to specific intervention start dates and data collection time points.…”
Section: Methodsmentioning
confidence: 99%
“…Focus groups and interviews for the process evaluation were scheduled to be conducted three months after the intervention period (objectives 2-4). Detailed information on the study design and rationale are reported elsewhere [30], and the original study protocol is attached as a S1 Protocol.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations